Women perceptions on the comprehensive care in the context of prevention of cervical cancer - Maria Gleiciane Lima Rocha; Andrea Gomes Linard (Rev Rene)
Objective: to know the perceptions of women on the comprehensive health care in the context of prevention of cervical cancer. Methods: this is a qualitative study with 34 women. A semi-structured interview for data collection and content analysis technique for organization and interpretation were used. Results: the categories listed were: Completeness relationship with comprehensive care in health promotion, Prevention and early detection of cervical cancer; Actions developed to prevent cervical cancer; Actions for the prevention of cervical cancer and its sufficiency; Evaluations of women on the care for the prevention of cervical cancer. Conclusion: women participants acknowledged the completeness as important for quality and effectiveness of prevention of cervical cancer.